States of Aggregation and Phase Transformation Behavior of Metallosurfactant Complexes by Hexacyanoferrate(II): Thermodynamic and Kinetic Investigation of ETR in Ionic Liquids and Liposome Vesicles - Karuppiah Nagaraj; Subramanian Sakthinathan; Te-Wei Chiu; Subramaniam Kamalesu; Snehal Lokhandwala; Nikhil M. Parekh; Chelladurai Karuppiah (Biomimetics, 2022)
Electronic absorption spectroscopy was used to study the ETR of surfactant–cobalt(III) complexes containing imidazo[4,5-f][1,10]phenanthroline, dipyrido[3,2-d:2′-3′-f]quinoxaline and dipyrido[3,2-a:2′,4′-c](6,7,8,9-tetrahydro)phenazine ligands by using ferrocyanide ions in unilamellar vesicles of dipalmitoylphosphotidylcholine (DPPC) and 1-butyl-3-methylimidazolium bromide ((BMIM)Br), at different temperatures under pseudo-first-order conditions using an excess of the reductant. The reactions were found to be second-order and the electron transfer is postulated as occurring in the outer sphere. The rate constant for the electron transfer reactions was found to increase with increasing concentrations of ionic liquids. Besides these, the effects of surfactant complex ions on liposome vesicles in these same reactions have also been studied on the basis of hydrophobicity. We observed that, below the phase transition temperature, there is an increasing amount of surfactant–cobalt(III) complexes expelled from the interior of the vesicle membrane through hydrophobic effects, while above the phase transition temperature, the surfactant–cobalt(III) complexes are expelled from the interior to the exterior surface of the vesicle. Kinetic data and activation parameters are interpreted in respect of an outer-sphere electron transfer mechanism. By assuming the existence of an outer-sphere mechanism, the results have been clarified based on the presence of hydrophobicity, and the size of the ligand increases from an ip to dpqc ligand and the reactants become oppositely charged. In all these media, the ΔS# values are recognized as negative in their direction in all the concentrations of complexes employed, indicative of a more ordered structure of the transition state. This is compatible with a model in which these complexes and [Fe(CN)6]4− ions bind to the DPPC in the transition state. Thus, the results have been interpreted based on the self-aggregation, hydrophobicity, charge densities of the co-ligand and the reactants with opposite charges.